2017
DOI: 10.21873/anticanres.11825
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Role of MiR-140-5p for the Treatment of Non-small Cell Lung Cancer

Abstract: Novel direct targets of miR-140-5p have not been investigated in this study, but our results indicate the involvement of miR-140-5p in lung cancer invasion. The preliminary data from this study imply that when miR-140-5p levels are restored; maybe synergistically support current therapies for NSCLC though further validation, especially in vivo is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 7 publications
2
19
0
Order By: Relevance
“…It acts by inhibiting the anti-apoptotic Ras signaling cascade (249). Recent studies confirmed also that the loss of regulation of ncRNAs is involved in chemoresistant acquisition (250, 251). The GAS5 lncRNA is implicated in chemoresistance modulation of several different drugs included into this subnetwork (179182).…”
Section: Drugs/non-coding Rnas Subnetworkmentioning
confidence: 76%
“…It acts by inhibiting the anti-apoptotic Ras signaling cascade (249). Recent studies confirmed also that the loss of regulation of ncRNAs is involved in chemoresistant acquisition (250, 251). The GAS5 lncRNA is implicated in chemoresistance modulation of several different drugs included into this subnetwork (179182).…”
Section: Drugs/non-coding Rnas Subnetworkmentioning
confidence: 76%
“…[24][25][26] Furthermore, previous studies have indicated that miR-140 can enhance chemosensitivity of some cancers. [27][28][29] Given this, we studied the potential role of miR-140 in reversing the cisplatin resistance of NSCLC. In the present study, we proved that our established cisplatin-resistant NSCLC cells showed significant resistance to cisplatin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] Furthermore, previous studies have indicated that miR-140 can enhance chemosensitivity of some cancers including NSCLC. [27][28][29] On the other hand, patients may benefit from miR-140, because miR-140 can attenuate the acute kidney injury induced by cisplatin through the Nrf2/ARE pathway. 30 Here, we investigated the effect of miR-140 on reducing the cisplatin-resistance of NSCLC and then explored the potential mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Low levels of miRNA-140 correlated with increased sensitivity to etoposide and topotecan in cell lines [155]. Although it has been proposed that it may serve as a tumor suppressive role via VEGF, forced overexpression of miRNA-140-5p in NSCLC cells reduced migration suggesting enhanced sensitivity to gefitinib, DMH1, and cisplatin [156]. Further studies will clarify the role of miR-140-5p in the response of NSCLC to treatment.…”
Section: Mirna-140 Levels Correlate To Chemosensitivity Of Nsclcmentioning
confidence: 96%